Anti-inflammatory action of Athyrium multidentatum extract suppresses the LPS-induced TLR4 signaling pathway. (10th May 2018) - Han, Xiong-Zhe; Ma, Rui; Chen, Qi; Jin, Xin; Jin, Yuan-Zhe; An, Ren-Bo; Piao, Xuan-Mei; Lian, Mei-Lan; Quan, Lin-Hu; Jiang, Jun
Abstract: Ethnopharmacological relevance: The aerial part of Athyrium multidentatum (Doll.) Ching (AM) is widely used in the northeastern region of China as an edible wild herb, but its medicinal value, especially its anti-inflammatory effect, has not been fully explored. Aim of the study: To investigate the anti-inflammatory activity of AM and clarify the anti-inflammatory mechanism involving the TLR4 signaling pathway using a lipopolysaccharide (LPS)-induced inflammatory model. Materials and methods: AM ethanol extract was used as the experimental material to investigate the effect that the extract has on the production of pro-inflammatory mediators (NO, PGE2, TNF-α, IL-1β and IL-6); changes in LPS-induced peritoneal macrophages (PMs); and TLR4-mediated intracellular events, including MAPKs (ERK, JNK, and p38) and IκB-α in the MyD88-dependant pathway and IRF3, STAT1, and STAT3 in the TRIF-dependent pathway. In in vivo experiments, we established an LPS-induced acute lung injury (ALI) model and investigated the cell count and cytokine (TNF-α, IL-1β and IL-6) levels in bronchoalvelar lavage fluid (BALF) of C57BL6 mice. Histological changes in the lung tissues were observed with H&E staining. Results: AM extract inhibited NO and PGE2 by suppressing their synthetase (iNOS and COX-2) gene expression in LPS-induced PMs; the secretion of IL-6, IL-1β, and TNF-α also deceased via the down-regulation of mRNA levels. Furthermore, the TLR4-mediated intracellular events involved the phosphorylated forms of MAPKs (ERK, JNK) and IκB-α in the MyD88-dependent pathway and the TRIF-dependent pathway (IRF3, STAT1, STAT3), and the relevant proteins were expressed at low levels in the AM extract groups. In in vivo experiments, the cell count and cytokine (TNF-α, IL-1β and IL-6) levels in BALF decreased significantly in a dose-dependent manner in the AM extract groups. The lung tissue structure exhibited dramatic damage in the LPS group, and the damaged area decreased in the AM extract groups; in particular, the effect of 10 mg/kg extract was similar to that of the positive control dexamethasone (DEX). Conclusion: The findings demonstrate that AM protects against LPS-induced acute lung injury by suppressing TLR4 signaling, provide scientific evidence to support further study of the safety of anti-inflammatory drugs and indicate that AM can be used as an anti-inflammatory and anti-injury agent to prevent pneumonia caused by microbial infection. Graphical abstract: